Induction and quantification of prefrontal cortical network plasticity using 5 Hz rTMS and fMRI - Esslinger, Christine (Hum Brain Mapp, 2012)
Neuronal plasticity is crucial for flexible interaction with a changing environment and its disruption is thought to contribute to psychiatric diseases like schizophrenia. High‐frequency repetitive transcranial magnetic stimulation (rTMS) is a noninvasive tool to increase local excitability of neurons and induce short‐time functional reorganization of cortical networks. While this has been shown for the motor system, little is known about the short‐term plasticity of networks for executive cognition in humans. We examined 12 healthy control subjects in a crossover study with fMRI after real and sham 5 Hz rTMS to the right dorsolateral prefrontal cortex (DLPFC). During scanning, subjects performed an n‐back working memory (WM) task and a flanker task engaging cognitive control. Reaction times during the n‐back task were significantly shorter after rTMS than after sham stimulation. RTMS compared with sham stimulation caused no activation changes at the stimulation site (right DLPFC) itself, but significantly increased connectivity within the WM network during n‐back and reduced activation in the anterior cingulate cortex during the flanker task. Reduced reaction times after real stimulation support an excitatory effect of high‐frequency rTMS. Our findings identified plastic changes in prefrontally connected networks downstream of the stimulation site as the substrate of this behavioral effect. Using a multimodal fMRI‐rTMS approach, we could demonstrate changes in cortical plasticity in humans during executive cognition. In further studies this approach could be used to study pharmacological, genetic and disease‐related alterations. Hum Brain Mapp 35:140–151, 2014. © 2012 Wiley Periodicals, Inc.